Analisis Hubungan Dukungan Pengawas Minum Obat TB-Paru dengan Kesembuhan Melalui Studi Epidemiologi Bersifat Analitik - Maharso Maharso; Zulfikar Ali As; Imam Santoso (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2015)
Abstract : Analysis Of Relationship Between Supporting The Observer Of  Pulmonary Tb Treatment With Cured By Analitycal Epidemiological Studies. Pulmonary Tuberculosis is a communicable disease which are virulent and lethal. One of ten latent infections (hidden) will develop into active disease, which if not treated properly will be fatal for the patient. Most of TB patients can be recovered, if they meet the applicable provisions of the treatment. Epidemiological studies about relationship between supporting the observer of  pulmonary tb treatment with cured in Puskesmas Purwodadi I Kabupaten Grobogan, prove not associated statistically. While in Puskesmas Mangkang Semarang Barat, shows there is significantly association between supporting the observer of  pulmonary tb treatment with cured. The problem is which one of the finding be able to be the base of decision making in management of pulmonary TB program nationally. The purpose of this study was getting explanation and base of decision making, whether the finding in 2 puskesmas which produce different finding be able to be base of general decision making (inferensial). The epidemiological study used systematic review methods. Source of research data was from the literature, obtained through the Internet, relevant research, especially research in Puskesmas Purwodadi I Kabupaten Grobogan dan di Puskesmas Mangkang Semarang Barat. The result showed that epidemiological study in both Puskesmas Purwodadi I and Puskesmas Mangkang had some similiarity that were analytical, used chi–square test, and in the method of sampling (Non Probability).  While in other study method was different, both in study design, number of sample, and the respondent's age criteria. Finding of epidemiological study in both Puskesmas Purwodadi I and Puskesmas Mangkang is inferential, so that only are specific site and does not apply to other population. Keywords : analitycal epidemiology, pulmonary-tb